Diversity of Gene Clusters for Polyketide and Nonribosomal Peptide Biosynthesis Revealed by Metagenomic Analysis of the Yellow Sea Sediment - Wei, Yongjun; Zhang, Lei; Zhou, Zhihua; Yan, Xing (Frontiers in Microbiology, 2018)
Polyketides (PKs) and nonribosomal peptides (NRPs) are widely applied as drugs in use today, and one potential source for novel PKs and NRPs is the marine sediment microbes. However, the diversities of microbes and their PKs and NRPs biosynthetic genes in the marine sediment are rarely reported. In this study, 16S rRNA gene fragments of the Yellow Sea sediment were analyzed, demonstrating that Proteobacteria and Bacteroidetes accounted for 62% of all the bacterial species and Actinobacteria bacteria which were seen as the typical PKs and NRPs producers only accounted for 0.82% of all the bacterial species. At the same time, PKs and NRPs diversities were evaluated based on the diversity of gene fragments of type Ⅰ polyketide synthase (PKS) ketosynthase domain (KS), nonribosomal peptide synthetase (NRPS) adenylation domain (AD) and dTDP-glucose-4,6-dehydratase (dTGD). The results showed that AD genes and dTGD genes were abundant and some of them had less than 50% identities with known ones; By contrast, only few KS genes were identified and most of them had more than 60% identities with known KS genes. Moreover, one 70,000-fosmid clone library was further constructed to screen for fosmid clones harboring PKS or NRPS gene clusters of the Yellow Sea sediment. Nine selected fosmid clones harboring KS or AD were sequenced, and three of the clones were assigned to Proteobacteria. Though only few Actinobacteria 16S rRNA gene sequences were detected in the microbial community, five of the screened fosmid clones were assigned to Actinobacteria. Further assembly of the 9 fosmid clones resulted in 11 contigs harboring PKS, NRPS or hybrid NPRS-PKS gene clusters. These gene clusters showed less than 60% identities with the know ones and might synthesize novel natural products. Taken together, we revealed the diversity of microbes in the Yellow Sea sediments and found that most of the microbes were uncultured. Besides, evaluation of PKS and NRPS biosynthetic gene clusters suggested that the marine sediment might have the ability to synthesize novel natural products and more NRPS gene clusters than PKS gene clusters distributed in this environment.